Autoimmune cytopenias following allogeneic hematopoietic stem cell transplant in pediatric patients: Response to therapy and late effects. Issue 9 (13th July 2020) - Koo, Jane; Giller, Roger H.; Quinones, Ralph; McKinney, Christopher M.; Verneris, Michael R.; Knight‐Perry, Jessica
Abstract: Background: Autoimmune cytopenias (AICs) are rare, but serious complications of allogeneic hematopoietic cell transplantation (allo‐HSCT). Procedure: We performed a case‐control study using 20 pediatric AIC cases and 40 controls, matched by stem cell source and primary indication comparing clinical and transplant characteristics, treatment, outcomes, and late effects. Results: Cases were more likely to be human leukocyte antigen mismatched ( P = 0.04). There was no difference in conditioning regimen, serotherapy use, graft‐versus‐host disease (GVHD) prophylaxis, incidence of acute or chronic GVHD, ABO compatibility, infections, and donor engraftment. The median time to AIC onset was 219 days (range, 97‐1205 days) and AIC resolution was 365 days (range, 10 days to 2737.5 days). First‐line therapies for AIC patients most commonly included corticosteroids (75%) and rituximab (55%). Only 25% of patients responded to first‐line treatment. At a median of 611.5 days from last rituximab dose, 82.5% patients were still receiving intravenous immune globulin for hypogammaglobulinemia compared with 2.5% of controls ( P < 0.0001). Iron overload was higher in AIC patients ( P = 0.0004), as was avascular necrosis ( P = 0.04). There was no difference in overall survival at one year after HSCT (85% vs 82.5%). Two patients with refractory autoimmune hemolytic anemia responded to daratumumab and had resolution of B‐cell aplasia. Conclusions: In this study, we find poor initial responses to AIC‐directed therapies and significant late effects.